Revisiting the Green City Concept in the Tropical and Global South Cities Context: The Case of Indonesia - Zain, Alinda F. M.; Pribadi, Didit O.; Indraprahasta, Galuh S. (Frontiers in Environmental Science, 2022)
Urban areas play a key role in reaching global sustainability as they produce a high number of waste and emission, consume a lot of resources, and perform as the prime mover of global economy. Unsustainable urbanization will bring multidimensional impacts on high spatiotemporal ranges which nearly impossible to be managed. As a preemptive action, urban sustainability has been considered as one of the most important targets in the Sustainable Development Goals. Within this context, green city has emerged as a widely adopted concept around the globe. In the Global North, green city has been incrementally developed into smart-compact-green city with efforts to mainstreaming green infrastructure and nature-based solutions in supporting ecosystem services. Quite the contrary, in the Global South cities, due to their rapid and vast urbanization process, green city has been fragmentally adopted in the form of green building, green technology, and green open spaces which are not fully integrated into the physical urban expansion. Previous studies have tried to portray the gap between cities in the Global North and in the Global South in implementing green city and to identify three underlying factors that might cause the gap, i.e., urbanization, biophysics, and governance. Still, how to deal with these factors and closing the gap remains questions to be addressed. This study aims to response to these questions based on the experience of green city experimentation in Indonesia. An exploratory study was done based on literature review and participant observation. The results show that the green city program was only focused on complying 30% area of green open spaces which at the end was unable to improve urban environment and sustainability. Local socio-ecological aspects coupled with integrated multilevel and multi-actors’ governance are recommended to increase the green city performances.